Uso del citrato de piperacina en la ascariasis de enfermos con fiebre tifoidea - Peña-Chavarria, Antonio; Lizano, Cecilia; Xirinachs, Hilda (Revista de Biología Tropical, 1956)
A clinical-parasitological study is presented of the effects of piperazine citrate on 36 typhoid fever patients heavily parasitized by Ascaris lumbricoides. The patient ages ranged from 4 to 70 years. Total doses varied from 1,5 to 6 grams. Complete negativization was achieved in 20 patients on whom coprological records were kept. The treatment is considered valuable, especially in reducing the danger of intestinal perforation by Ascaris, which would be greater in typhoid fever cases.